2011
DOI: 10.1016/j.tripleo.2010.12.023
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemical profile of oral inflammatory myofibroblastic tumors

Abstract: Within the results encountered, the present panel should be of great assistance in the diagnosis of oral IMTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The immunohistochemical profile for IMFT shows variable staining for SMA, MSA, and desmin; the nuclear positivity to ALK is observed in approximately 50-60% of cases, demonstrating a strong correlation with ALK gene rearrangement. In our case, the positivity to MYOD1 and Caldesmon and negativity to Alk exclude the diagnosis [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 91%
“…The immunohistochemical profile for IMFT shows variable staining for SMA, MSA, and desmin; the nuclear positivity to ALK is observed in approximately 50-60% of cases, demonstrating a strong correlation with ALK gene rearrangement. In our case, the positivity to MYOD1 and Caldesmon and negativity to Alk exclude the diagnosis [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 91%
“…Among the most pronounced changes were the proteins implemented in contractile activity and formation of actin cytoskeleton such as CALD1, CNN‐2, ML12A and COF1. CALD1 participates in the interaction of actin and myosin and its expression and function in MFs has been studied (Lazard et al., ; Kalekou et al., ; Hai and Gu, ; Council and Hameed, ; Huang et al., ; Leung et al., ; Salgueiredo‐Giudice et al., ). Elevated expression of this protein was also observed in oral SCCs (Méndez et al., ) and its overexpression was associated with lymph node metastasis and poor prognosis in patients with oral cavity SCC (Chang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that myofibroblasts, particularly in more advanced stages of differentiation, may express antigens seen in smooth muscle cells 23 , 25 , revealing that the pattern of expression of these proteins may vary depending on the site and nature of the pathological process. Typically, myofibroblasts are negative for cytokeratins (epithelial cell markers), CD68 (monocyte/ macrophage marker), CD31 (endothelial cell marker), and CD34 4 , 12 , 26 .…”
Section: Literature Reviewmentioning
confidence: 99%